2012
DOI: 10.1016/j.molbiopara.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Excretory/secretory products from in vitro-cultured Echinococcus granulosus protoscoleces

Abstract: Cystic hydatid disease (CHD) is caused by infection with Echinococcus granulosus metacestodes and affects humans and livestock. Proteins secreted or excreted by protoscoleces, pre-adult worms found in the metacestode, are thought to play fundamental roles in the host-parasite relationship. In this work, we performed an LC-MS/MS proteomic analysis of the excretory-secretory products obtained from the first 48 h of an in vitro culture of the protoscoleces. We identified 32 proteins, including 18 that were never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 50 publications
7
76
2
Order By: Relevance
“…Both proteins have already been identified by proteomic analyses of E. granulosus hydatid fluid (Aziz et al, 2011;Monteiro et al, 2010) and in vitro ES products of protoscoleces (Virginio et al, 2012). Here, these proteins were detected accordingly, both in the hydatid fluid (containing ES products of the germinal layer and protoscolex) and in the ES products from in vitro cultures of protoscoleces.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Both proteins have already been identified by proteomic analyses of E. granulosus hydatid fluid (Aziz et al, 2011;Monteiro et al, 2010) and in vitro ES products of protoscoleces (Virginio et al, 2012). Here, these proteins were detected accordingly, both in the hydatid fluid (containing ES products of the germinal layer and protoscolex) and in the ES products from in vitro cultures of protoscoleces.…”
Section: Discussionmentioning
confidence: 62%
“…To obtain excretory-secretory (ES) products, protoscoleces were cultivated similarly as described by Virginio et al (2012), with some modifications. Protoscoleces were cultured in 4 ml of RPMI medium for 48 h, at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Two proteomic studies on the zoonotic pathogen E. granulosus found that an annexin was present in the ES product and hydatid cyst fluid. 22,23 Therefore, we performed a primary study characterizing the Eg-ANX gene and validated the secretory and calcium ion binding properties of Eg-ANX protein.…”
Section: Discussionmentioning
confidence: 99%
“…15,21 Recently, proteomic research on E. granulosus has shown that annexin B33 protein (Eg-ANX) could be detected in the excreted/secreted (ES) product and hydatid cyst fluid, which might potentially play important roles in parasite survival mechanisms during infection. 22,23 However, the secretory properties of Eg-ANX in the proteomic research on E. granulosus was not very specific. In this study, we validated the existence of Eg-ANX in hydatid cyst fluid and found that Eg-ANX could be secreted in the host-derived layer (granulation tissue) of host liver.…”
Section: Introductionmentioning
confidence: 99%
“…In E. granulosus, EgAgB3 was abundantly transcribed in the protoscolex (38), but secretion into the hydatid fluid was minimal at the protein level (25,39). The differential expression patterns of AgB3 in phylogenetically close neighbors imply that an as-yet-unknown transcriptional regulatory mechanism operates in different manners during the maturation of EmAgB3 and EgAgB3.…”
Section: Discussionmentioning
confidence: 99%